Tea polyphenols alleviate tri‐ortho‐cresyl phosphate‐induced autophagy of mouse ovarian granulosa cells. Issue 4 (2nd December 2019) - Yang, Si; Shao, Shuxin; Huang, Boshu; Yang, Dan; Zeng, Lin; Gan, Yu; Long, Dingxin; Chen, Jiaxiang; Wang, Jinglei
Abstract: Tri‐ortho‐cresyl phosphate (TOCP), a widely used plasticizer in industry, can cause female reproductive damage. Tea polyphenols (TPs) have multiple health effects via inhibiting oxidative stress. However, the reproductive protection of TPs in TOCP‐induced female reproductive system damage is yet to be elucidated. In the study, TOCP inhibited cell viability and induced autophagy of mouse ovarian granulosa cells; while TPs could rescue the inhibition of viability and induction of autophagy. 3‐MA, an autophagy inhibitor, could also rescue the inhibition of cell viability. These results indicated that TPs played a protective role in TOCP‐induced autophagy. Furthermore, TPs could inhibit the induction of oxidative stress of the cells by TOCP, which implying that TPs might alleviate TOCP‐induced autophagy via inhibiting oxidative stress. Furthermore, TPs could rescue TOCP‐induced autophagy and oxidative stress in the mouse ovarian tissues. Taken together, these results indicated that TPs could protect TOCP‐induced ovarian damage via inhibiting oxidative stress.